2018
DOI: 10.1002/bmc.4334
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Sijunzi decoction in rat plasma after oral administration using ultra‐high‐performance liquid chromatography electrospray ionization quadrupole–time of flight mass spectrometry

Abstract: Sijunzi decoction (SJZD) is one of the most well-known traditional Chinese herbal formulations. This study elucidates the pharmacokinetics of SJZD in rat plasma after the administration of a single oral dose of 3 mL/kg using ultra-high-performance liquid chromatography electrospray ionization quadrupole-time of flight mass spectrometry (UHPLC-ESI-Q-TOF/MS) with bergapten as an internal standard. The separation was performed on an Agilent Zorbax Eclipse Plus C column (2.1 × 50 mm, 1.8 μm) by elution with aceton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Typically, six major fragment ions were generated from the parent ion directly at m / z 803.3866, 645.3647, 469.3382, 351.0569, and 193.0355, which corresponded to m / z 803.3866 [M − H − H 2 O] − , 645.3604 [M − H − C 6 H 8 O 6 ] − , 469.3315 [M − H − 2C 6 H 8 O 6 ] − , 351.0571 [2C 6 H 8 O 6 ] − and 193.0355 [C 6 H 10 O 7 − H] − , respectively. Compared with a previous study (Qu et al, 2018), C101 was identified as glycyrrhizic acid. Figure 3e shows the production spectra and the potential MS/MS fragmentation pathway.…”
Section: Resultscontrasting
confidence: 75%
“…Typically, six major fragment ions were generated from the parent ion directly at m / z 803.3866, 645.3647, 469.3382, 351.0569, and 193.0355, which corresponded to m / z 803.3866 [M − H − H 2 O] − , 645.3604 [M − H − C 6 H 8 O 6 ] − , 469.3315 [M − H − 2C 6 H 8 O 6 ] − , 351.0571 [2C 6 H 8 O 6 ] − and 193.0355 [C 6 H 10 O 7 − H] − , respectively. Compared with a previous study (Qu et al, 2018), C101 was identified as glycyrrhizic acid. Figure 3e shows the production spectra and the potential MS/MS fragmentation pathway.…”
Section: Resultscontrasting
confidence: 75%
“…On the basis of the qualitative study and network pharmacology, the characteristic parameters of 20 main chemical components were investigated by the MRM analysis method, including parent ion, daughter ion, declustering potential, and collision energy. In order to satisfy the simultaneous quantification of multiple components, taking into account the response of different chemical components in MRM mode and the content differences in LGZG, the DP and CE of some chemical components were dynamically adjusted, as detailed in Table 3 [ 31 37 ]. Multiple reaction monitoring chromatograms of the control and sample solutions are shown in Figure 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no washout periods in this study, we considered that the carryover effects of modified SJZD have little effect in practice. The reasons are as follows: (1) the main active ingredients of SJZD are glycyrrhizic acid, glycyrrhetinic acid, pachymic acid, atractylodes lactone III, ginsenoside Re, and ginsenoside Rb 1 , and a pharmacokinetic study showed that their mean half-life is no more than 12 h [38]. For the other active ingredients of modified SJZD, further studies reported that their half-life is no more than 24 h [39][40][41][42][43][44][45] and (2) even if there are carryover effects for modified SJZD, a mixed-effect model will be used to analyse the data from the N-of-1 trials.…”
Section: Discussionmentioning
confidence: 99%